Nucleation and growth of discontinuous precipitates in Cu–Ag alloys. (1st February 2022) - An, Bailing; Xin, Yan; Niu, Rongmei; Xiang, Zhaolong; Wang, Engang; Han, Ke
Abstract: To study discontinuous precipitation, which is an important method for strengthening materials, we observed the nucleation and growth of discontinuous precipitates in Cu–Ag alloys using electron backscatter diffraction and scanning transmission electron microscopy. We found that discontinuous precipitation always started with Ag precipitates, which nucleated on Cu grain boundaries. These precipitates then each took the shape of a large, abutted cone that shared a semi-coherent interface with one of the Cu grains, topped by a small spherical cap that shared an incoherent interface with the Cu grain on the opposite side of the boundary. This formation created a difference between the levels of interface energy on each side of boundary. We assume that this difference and boundary curvature together generates the driving force necessary to push grain boundary migration, thus triggering discontinuous precipitation. Because of grain boundary migration, Ag solute was consumed at one side of the grain, which causes a solute difference. The difference produces mainly driving force, pushing the boundaries to migrate forward.